Leadership roles in managing change towards academic excellence at the branch campus / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (2008)
Leadership roles are of prime importance in determining the destiny of an organization particularly when dealing with change efforts. This paper discusses the current leadership situation in UiTM Pahang and tries to relate the leadership roles in managing change in order to achieve academic excellence. Some recommendations are proposed to enhance the leadership functions and roles to facilitate the university's efforts in achieving academic excellence and attain the status of world-class university.